2021
DOI: 10.1101/2021.07.28.454203
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparing cortex-wide gene expression patterns between species in a common reference frame

Abstract: Advances in sequencing techniques have made comparative studies of gene expression a current focus for understanding evolutionary and developmental processes. However, insights into the spatial expression of genes have been limited by a lack of robust methodology. We therefore developed a set of algorithms for quantifying and comparing tissue-wide spatial patterns of gene expression within and across species. Here we apply these algorithms to compare cortex-wide expression of Id2 and RZRβ mRNA in early postnat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Importantly, these patterns appear to be conserved across mammalian species ( Fulcher et al, 2019 ), which opens up the possibility of using the expression of homologous genes as a common space across species. In fact, a recent study demonstrated how the expression of homologous genes can be used to directly register mouse and vole brains into a common reference frame, which allows for direct point-by-point comparisons of brain maps ( Englund et al, 2021 ). However, this specific approach is only feasible because of the large degree of morphological similarity between mouse and vole brains.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, these patterns appear to be conserved across mammalian species ( Fulcher et al, 2019 ), which opens up the possibility of using the expression of homologous genes as a common space across species. In fact, a recent study demonstrated how the expression of homologous genes can be used to directly register mouse and vole brains into a common reference frame, which allows for direct point-by-point comparisons of brain maps ( Englund et al, 2021 ). However, this specific approach is only feasible because of the large degree of morphological similarity between mouse and vole brains.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, these patterns appear to be conserved across mammalian species (28) , which opens up the possibility of using the expression of homologous genes as a common space across species. In fact, a recent study demonstrated how the expression of homologous genes can be used to directly register mouse and vole brains into a common reference frame, which allows for direct point-by-point comparisons of brain maps (29) . However, this specific approach is only feasible because of the large degree of morphological similarity between mouse and vole brains.…”
Section: Introductionmentioning
confidence: 99%
“…The recent availability of large open image datasets of rodents 25 , non-human primates 26,27 , human subjects 28,29 and fossil taxa 30 has facilitated comparative analyses of brain organisation and function 31,32 . However, studies are either limited to phylogenetically closely related species 33,34 , a-priori defined spatial homologies 6,35 , or avoid establishing correspondences between morphologically and functionally divergent domains altogether by focusing on global descriptions of brain organisation 5,[36][37][38] .…”
mentioning
confidence: 99%